Neonatal Purpura Fulminans - Sharma, D; Yadav, J (Journal of Nepal Paediatric Society, 2014)
Neonatal purpura fulminans is a rare, life-threatening condition of dermal microvascular thrombosis associated with DIC and perivascular hemorrhage in the newborn period associated with high morbidity and mortality [1]. Gram negative organisms and Staphylococcus species are the most common causes of the acute infectious type [2]. It may be congenital, as a result of protein C and S deficiency, or acquired due to severe infection. It is characterized by the rapid spread of symmetrical, bluish-black hemorrhages into the skin, affecting mainly the extensor surfaces of the extremities and showing a tendency to deep necrosis and the formation of sero-sanguineous bullae. The haemorrhagic areas are well defined and are surrounded by oedema. These lesions are accompanied by a high fever and intense systemic symptoms. DOI: http://dx.doi.org/10.3126/jnps.v34i1.8975 J Nepal Paediatr Soc 2014;34(1):80